Knowledge-based decision support system for improving e-business innovations and dynamic capability of IT project management. Issue 2 (3rd April 2019) - Yan, Min-Ren; Tran-Danh, Nhan; Hong, Lin-Ya
ABSTRACT: E-business and e-commerce services have been globally applied across various industries in the digital era. Leading e-commerce platform companies should invite open innovation to explore new market and continuously innovate their products and services with various supply chains that simultaneously require more reliable and flexible project management for the IT supports. The e-businesses are urging for agile and dynamic approach that integrate the time, cost, and quality objectives and human resources in the IT team. This research proposes a knowledge-based management decision support system, by using System Dynamics modelling and computer simulations, to analyse project performance over time and the impacts of strategic management decisions on the dynamic capability of e-commerce services. A real world case study, from a cross-border e-commerce platform company, has been investigated. Operations strategies to e-business innovations and IT supports could be timely evaluated with iterative simulations. The project management competency, service quality, operations cost feasibility, and profitability of e-commerce services could be further improved with the model applications.